Disseminated Intravascular Coagulation in Gastroenteritis - S. Setiadharma; T. Himawan (Paediatrica Indonesiana, 1975)
Four children, 3 males and 1 female, varying in ages from 3 to 12 years, showing the shock syndrome in gastroenteritis accompanied by intravascular coagulation (DIC) are reported. All patients developed progressive thrombocytopema, prolonged prothrombin time as well as partial thromboplastin time; and a decreased content of fibrinogen in the blood several days after hospitalization was observed. The diagnosis and treatment of DIC are also discussed.